Analisis Keterampilan Berpikir Kritis Siswa Setelah Menerapkan Model Pembelajaran PBL (Problem Based Learning) - Siti Badriyah; Zaini Hartika; Gusmanelli Gusmanelli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the implementation of the Problem Based Learning (PBL) model in enhancing the critical thinking abilities of 4th-grade students. The research employs a descriptive qualitative approach with data collection techniques such as observation, interviews with mentor teachers, and documentation. The results of the study indicate that the implementation of PBL has a positive impact on developing students' critical thinking skills. Students are accustomed to facing real-world problems, analyzing situations, and seeking relevant and rational solutions. Furthermore, this learning model also enhances students' communication and collaboration skills as they engage in group discussions to solve problems collectively. However, challenges in its implementation lie in time management and ensuring the active participation of all students in the learning process. Overall, this study demonstrates that PBL is effective in developing students' critical thinking abilities, as well as improving their social and communication skills, which are essential in daily life.